The parameters of poetry translation: A stylistic analysis of the linguistic and literary techniques used in the translations of the Odyssey and the Iliad - Ilyas, Sobia (The Journal of Humanities & Social Sciences, 2022)
The paper posits that Poetry Translation is an unimpeded and uninhibited genre of Translation Studies which allows immense freedom to the translator to perceive and project the source text according to her social, cultural, and moral sensibilities and above all her aesthetic tendencies. This stance is supported through a diachronic and synchronic evaluation of diverse translations of selected passages of Homeric epics: the Iliad and the Odyssey. The research draws upon Eugene Nida’s sociolinguistic approach to translation and his concept of Dynamic Equivalence for the interpretation and analysis of the Homeric texts. In doing so, the researcher highlighted the various literary techniques and approaches used by three renowned translators of Homeric epics: George Chapman, Alexander Pope, and Robert Fitzgerald, through a stylistic analysis and explored the socio-cultural factors behind their choice of translation strategies. The findings reiterated the viewpoint that poetry translators over the centuries have adopted fluid approaches to translating poetry in keeping with their individual perceptions regarding the principles that govern the craft of literary translation.